How Green Lean Six Sigma and Environmental Dispositions Support Circular Economy Practices - Mohammad Herman Sulistiyo; Ana Noveria; Qaisar Ali (SAN Scientific, 2026)
Despite growing interest in the circular economy (CE), strategic frameworks supporting its implementation in the financial sector remain underexplored. This limitation restricts banks’ ability to integrate circular principles with sustainability goals, operational efficiency, and long-term value creation. Previous studies have mainly focused on manufacturing and industrial sectors, with limited attention to how Green Lean Six Sigma (GLSS) and managers’ environmental beliefs support CE adoption in banking. Addressing this gap, this study investigates the direct effect of GLSS and the mediating role of managers’ environmental beliefs in facilitating CE implementation in banks, based on the Resource-Based View (RBV) theory. Data were collected from 713 managers in Malaysian banks and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that GLSS has a significant positive effect on CE implementation. Managers’ environmental beliefs significantly mediate the relationships between green and lean strategies and CE, while the mediation effect of Six Sigma is insignificant. These findings extend RBV theory by identifying GLSS as a strategic organizational resource and managers’ environmental beliefs as an important capability supporting CE implementation in the financial sector.